Effect of different origins of natural rubber on the properties of carbon black filled natural rubber composites. - Phanny, Yos
Two different origins of natural rubber (NR) from Malaysia; SMR CV60 and Vietnam; SVR 3L filled with 0 and 30phr carbon black (CB) were investigated. Compounds were prepared by a two roll mill with convential (CV) and efficient (EV) cure systems. Results obtained show taht SVR 3L has higher Mooney viscosity compared to SMR CV60. A different origin of NR has influenced the cure characteristics of rubber compounds. In EV system. SVR 3L compounds showed faster cure rate index (CRI) while in CV system showed contrary results. However, CRI of NR compounds with EV system increased with addition of CB due to high amount of accelerator while CRI in CV system decreased with addition of CB. Torque difference for both NR compounds with each cured system showed similar value. However, mechanical and physical properties were dependent on addition of CB. SVR 3L composites exhibited better tensile strength and recovery from loading force compared to SMR CV60.
Keywords: Cure characteristics; Mechanical properties; Natural rubber; Vulcanization systems